Klugheit Begriff - Konzepte - Anwendungen - Wegner, Gerhard; Scherzberg, Arno; Betsch, Tilmann; Walgenbach, Peter; Peukert, Helge; Thumfart, Alexander (Mohr Siebeck, 2008)
In the articles in this new volume, the authors deal with the basic principles of and the prerequisites for wise thinking, describe the position of the concept of wisdom in the context of various disciplines and show the functions attributed to it.
PublicationDate: 20211110
Keywords: Rationalität -- Klugheit -- Wissen -- Können -- Allgemeines -- Verfassungsrecht und Staatslehre